Vegetation structure, floristic composition and growth characteristics of Aucoumea klaineana Pierre stands as influenced by stand age and thinning - Fuhr, M.; Delegue, M.A.; Nasi, Robert (2001)
The coastal forest of Gabon abounds in monospecific secondary Aucoumea klaineana stands derived from natural regeneration after shifting cultivation. This paper aims to describe the changes in the structure and dynamics of these stands with age. It then assesses the impact of selective thinning in the upper storey on both structural and dynamic parameters. The experiment consisted of 34 Permanent Plots in stands from establishment to more mature stages (ca. 50 years old). Thirteen plots (17--45 years old) were thinned. More than 80% of the removal came from supernumerary dominant A. klaineana. A. klaineana represented 60% of the total density in stands ca. 15 years old but >90% of the dominant trees in older stands. The changes with age in the floristic composition of the unthinned stands showed three successional stages during which pioneer species associated with A. klaineana (from establishment to ca. 15 years) were progressively replaced by mature forest species. Basal area increased and density decreased with age before reaching stable values at ca. 40--45 years. Mortality was very high in young stands but decreased in the older ones. Mortality generally affected small diameter individuals in the dominated storey. Diameter and basal area increments showed that the stand growth resulted from the growth of dominant A. klaineana. Diameter increments of A. klaineana were elevated during the first years of colonisation (1.9 cm/year) and were still ca. 0.7 cm/year for 50-year-old dominant trees. Thinning did not increase the mortality of the dominant population. It favoured the individual growth of A. klaineana. The gain was substantial for dominated trees and small dominant trees (from 60 to 100%) but was lower for large dominant trees (ca. 25--30%). Therefore, stimulation of individual growth did not compensate for the loss of basal area at the stand level.